Analysis of the Translation Technique of German Humor Text into Indonesian Language on the Subtitle of the Film "Army Of Thieves" - Laras Asih (Asian Journal of Applied Education (AJAE), 2024)
This study aims to describe the translation of humorous texts from German to Indonesian Language in the movie "Army Of Thieves". The research on this translation uses a qualitative method with a descriptive approach. This study uses the theory of Molina and Albir (2002) which consists of 18 translation techniques. The conclusion of this study is that the group translation techniques used in this study such as single technique, pair technique, triple technique, and quartet technique. Of the four types of translation techniques, the pairing technique is the most commonly used to create equivalence in the text. The pairing technique was used in 11 sentences (84.62%). Other translation techniques are the triple technique of 1 sentence (7.69%) and the quartet technique of 1 sentence (7.69%).